Operating speed distributions in off-street cycling facilities by vehicle type and motorization - Amir Hassanpour; Alexander Bigazzi (Journal of Cycling and Micromobility Research)
With the growing popularity of motorized Personal Mobility Devices (PMDs) for urban travel, there is increasing need to understand the impacts on transportation facility operation. Speed is a critical aspect of vehicle performance, and the lack of robust information on PMD operating speeds hinders facility design, regulation, and policy for safe and comfortable PMD integration. The objectives of this study are 1) to derive operating speed distributions for all Personal Mobility Devices in use on off-street “cycling” facilities in metropolitan Vancouver, Canada, and 2) to determine how PMD speeds are influenced by microenvironment factors including facility type, path grade, weather, and path traffic volume. Classified speed data for 27 PMD types were collected in 4 seasons at 12 sampling locations in Vancouver, Canada. Results from the 25,053 observations show that motorization increases speeds by 3, 10, and 13 km/hr for bicycles, skateboards, and scooters, respectively, which tends to homogenize average speeds across PMD types at around 20–24 km/hr. Motorization also decreases the effect of grade on speed by about 2/3rd. Even with motorization, bicycle and other PMD speeds rarely exceed the regulatory limit of 32 km/hr – except for sit-down electric scooters which have exceptionally high speeds. Scenario analysis indicates that even with large penetration rates of motorized PMD, a 30 km/hr design speed for off-street paths would still be appropriate, although less conservative.